STUDENTS’ PUBLIC SPEAKING OBSTACLES IN JOINING INDONESIA INTERNATIONAL IOT OLYMPIAD (I3O) - Ilfa, Alfiya; Nurcahyo, Agung Dwi; Romadlon, Farid Noor (Universitas Bunda Mulia, 2024)
The study aimed to know students’ public speaking obstacles in joining Indonesia International IoT Olympiad (I3O) and strategies to overcome it. The study used qualitative research with case study design. It took 6 students from fourth and sixth semester. There were 3 students from English Education Department and 3 students from Non-English Education Department (Agriculture, Information Systems, and Mathematics Education) who joined I3O 2022. The researcher took offline and online competitions which is an online competition (judging session record) got when the researcher became a moderator in that event. The study used questionnaire, interview, and observation for the instruments. It found linguistic and non-linguistic obstacles in public speaking. Linguistic obstacles for English major and non-English major students are lack of grammar, lack of vocabulary, and lack of pronunciation. In non-linguistic obstacles, English major students faced inhibition, fear of making mistakes, felt nervous and anxiety, can’t cooperate with team, worried when they were answering questions from judges, fear that audience didn’t understand what they said, didn’t master the material, and confused to start speaking. While, Non-English major students faced inhibition, felt nothing to say, became low participation, use mother tongue, fear of making mistakes, nervous, anxiety, loss of self-confidence, can’t cooperate with team, worried when answer the questions from judges. English and non-English major students have strategies to overcome public speaking obstacles. There are gesturing, practicing, using note card, visualization, and preparation.